Advantage of priority regulation of pumped storage for carbon-emission-oriented co-scheduling of hybrid energy system. (February 2023) - Li, Xudong; Yang, Weijia; Zhao, Zhigao; Wang, Ran; Yin, Xiuxing
Abstract: Multi-energy co-scheduling is a crucial approach to promote variable renewable energy consumption and reduce carbon emission. In this paper, a co-scheduling model of Wind-Photovoltaic (PV)-Hydro-Thermal-Pumped storage hybrid energy system (HESWPHTP ) is constructed considering economy and carbon emission. Then, an operation mode of priority regulation of pumped storage (S2) for HESWPHTP is proposed. Furthermore, a wind plant, a PV plant, a general hydropower plant (GHP), a thermal power plant (TPP) and a pumped storage plant (PSP) in China's Jilin Province are selected as the simulation objects of HESWPHTP . Finally, the advantage of S2 is quantitatively analyzed by combining technical and economic indicators of both HESWPHTP and its subsystems. The typical day results show that the advantage of S2 is superior to S1 (i.e., operation mode without PSP). The annual simulation results show that compared with S3 (i.e., operation mode of priority regulation of GHP), both the annual average operating cost and carbon emission of HESWPHTP are reduced by 0.84% and 0.70% (i.e., enhanced the low-carbon economic performance of HESWPHTP ); the regulation mileage of GHP and the operation hours of TPP are respectively reduced by 30.33% and 4.07%, while the wear-and-tear of PSP is reduced by 5.44% when the startup and shutdown time of PSP remains the same as S3 (i.e., reduced the regulation intensity of the subsystems). Overall, this operation mode of S2 and its advantage assessment method may have potential value in the management of hybrid energy system. Highlights: An economic-carbon emission co-scheduling model of HESWPHTP is constructed. An operation mode of priority regulation of pumped hydro is proposed and assessed. The mode resulted in cost and carbon emission average decline of 0.84% and 0.70%. Regulation intensity of hydro and thermal power average decline of 30.33% and 4.07%. Wear-and-tear of pumped hydro average reduction of 5.44%.